Deferred Prosecution Agreement (DPA): Model Keadilan Bagi Korporasi dan Negara dalam Tindak Pidana Pajak - Kynan Raffael Daud; Mardian Putra Frans (Jurnal Hukum Lex Generalis, 2024)
The existence of criminal sanctions against tax crime is not always effective in therecovery of state loss. Therefore. There is a need for an approach that is moreoriented towards the recovery of state losses in handling tax crime. Cases of taxviolation have been resolved through formal legal processes that have weaknessdue to lack of room for state recovery because of the long and expensive process.This research uses a normative legal research method. The results showed that theDeferred Prosecution Agreement as a legal concept that allows postponement of thecriminal process with certain conditions that must be met by the defendant includingefforts to recover state losses. The application of DPA should be considered in therevision of KUHAP so that state losses can be recovered by the postponement ofprosecution method.